Magnetic Resonance Imaging (MRI) Lesion Patterns in Neuromyelitis Optica Spectrum Disorder (NMOSD) - Watcharakorn, Arvemas; Sukpairoh, Supawan; Mingkwansook, Varalee; Sukphulloprat, Puchit (Science & Technology Asia, 2022)
We aimed to describe MRI lesion patterns in cases of NMOSD, aiding diagnosis of the disease. We retrospectively examined 27 patients with NMOSD, done by two neuroradiologists evaluating spinal cord, optic nerve and brain lesions. The mean number of involved spinal cord vertebral segments was 8.32 ±4.77 and the median longitudinal length was 11.4 centimeters (6.8-20.2). Spinal cord involvement ≥ 3 vertebral segments was found in 89.47% of patients. Concerning the location of spinal cord lesions, 84.21% were cervical, 57.9% were thoracic, and 57.9% were covered cervicomedullary junction. All spinal cord lesions showed both central and peripheral involvement on axial distribution and 94.74% of spinal cord lesions involved more than 50% of the cross-sectional area. Bright spotty lesions were found in 42.11% of patients. Bilateral optic neuritis was found in 83.33% of patients. These lesions involved more than half of the optic nerve length in 63.64% of patients. Brain MRI abnormalities were found in 88% of patients. The most frequently involved area was deep/subcortical white matter (76%). The second most frequently involved area was periependymal surface (60%). MRI lesion patterns that are suggestive of NMOSD include longitudinal involvement of the spinal cord at three or more contiguous vertebral segments, both central and peripheral involvement on axial distribution which involves more than 50% as well as bilateral optic nerve involvement, and involvement in more than half of the optic nerve length. Cervical and cervicomedullary junction involvement seemed to be more common than thoracic involvement in Thai patients.